Identifikasi Malassezia furfur Pada Kerokan Kulit Anak-Anak Di Banjar Dinas Batang Karangasem Bali - Adelia, I Gusti Ayu Devi; Bintari, Ni Wayan Desi; Idayani, Sri (Jurnal Kesehatan Rajawali, 2025)
Tinea versicolor is a common superficial fungal infection found in tropical regions such as Indonesia. This condition is often caused by Malassezia furfur, especially in environments with high temperature and humidity and less than optimal hygiene. This study aimed to identify the presence of M. furfur in elementary school children in Banjar Dinas Batang, Karangasem, Bali, a region with a cool, humid climate and limited sanitation access. The study used a descriptive design with a purposive sampling approach, involving 23 children aged 6–18 years who showed skin lesion symptoms and had not undergone antifungal therapy. Skin scrapings were examined microscopically using a 10% KOH solution combined with Parker ink. Observations were made at 100× and 400× magnifications, identifying the distinctive morphology of M. furfur as a “spaghetti and meatballs” structure. Of the 23 samples examined, 13 (56.5%) tested positive for Malassezia furfur. The majority of cases occurred in boys (83%). Hygiene data showed that 61% bathed once a day, 78% changed clothes twice a day, but 87% washed clothes only once a week. Furthermore, most respondents (56%) used rainwater as their source of clean water. The relatively high prevalence of M. furfur infection reflects the strong influence of the humid environment, inadequate sanitation, and suboptimal hygiene behaviors. Microscopic examination using the KOH and Parker ink method proved effective as an initial screening tool in rural areas. Nevertheless, health education interventions and improved access to clean water are needed to reduce the incidence of skin fungal infections in children